Mechanical integrity of friction-riveted joints for aircraft applications. (15th January 2020) - Borba, N.Z.; Kötter, B.; Fiedler, B.; dos Santos, J.F.; Amancio-Filho, S.T.
Abstract: The predictability of damage evolution is a challenge for mechanical joints of composite structures due to the highly nonlinear material behavior. In this study, friction riveting was investigated as an alternative joining technology for composite laminates by analyzing experimentally the joint mechanical behavior under different loading scenarios. The failure and fracture micro-mechanisms of composite laminate single lap joints were studied under quasi-static and cyclic loading. The joints failed mainly by rivet detachment from the composite hole, followed by adhesive/cohesive failure of the squeezed material, and rivet pull-through failure. Despite lower quasi-static strength of friction-riveted joints (6.2 ± 0.3 kN) compared to reference bolted joints (8.7 ± 0.2 kN), their fatigue life was higher by 88%. The main improving contributions were: the squeezed material, working as an adhesive between the composite parts and an additional fracture micro-mechanism, and the absence of clearance at the rivet-composite interface, which promoted an improved load transfer between the joined parts.